2007
DOI: 10.1186/bf03352016
|View full text |Cite
|
Sign up to set email alerts
|

An aspect of the subsurface structure of the Burdur-Isparta area, SW Anatolia, based on gravity and aeromagnetic data, and some tectonic implications

Abstract: Gravity and aeromagnetic analyses were conducted in the Burdur-Isparta area of Turkey in order to identify the subsurface structure and tectonics of the region independent of surface cover. The analytic signal of the aeromagnetic anomalies was first calculated to delineate the source fields of these anomalies. The magnetic signatures were found to correlate well with the intrusives associated with the subduction of the African oceanic lithosphere and with the ophiolitic nappes in the region. The residual aerom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 49 publications
(58 reference statements)
1
14
0
1
Order By: Relevance
“…The crust in southwestern Anatolia thins from 34 km in the east to 22 km in the Aegean Sea (Saunders et al, 1998). Crustal thickness in the Isparta Angle area is 30-37 km (Kalyoncuoglu, 2001;Dolmaz, 2007;Erduran, 2009). For this reason, we assumed that earthquakes in the depth range 0-35 km occurred within the crust.…”
Section: Mapping B-valuementioning
confidence: 98%
“…The crust in southwestern Anatolia thins from 34 km in the east to 22 km in the Aegean Sea (Saunders et al, 1998). Crustal thickness in the Isparta Angle area is 30-37 km (Kalyoncuoglu, 2001;Dolmaz, 2007;Erduran, 2009). For this reason, we assumed that earthquakes in the depth range 0-35 km occurred within the crust.…”
Section: Mapping B-valuementioning
confidence: 98%
“…Aside from high Bouguer gravity anomalies due to their high densities, ophiolites have strong effects on magnetic anomalies due to their high magnetic susceptibilities (Rao et al, 2016). Numerous studies show that ophiolites usually have positive magnetic anomalies (Kane et al, 2005;Dolmaz, 2007;Rao et al, 2016); thus, comparing magnetic and Bouguer gravity anomaly maps of the Çumra area would support the buried ophiolite thesis. An examination of the area's aeromagnetic data points out a strong magnetic anomaly around the Çumra region as seen in Figure 10 (MTA, 2007).…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, our LVZ is interpreted to represent a body of partial melt in the lower-crust, which is consistent with patterns of volcanism at the surface. Comparable magmatic bodies within extensional provinces with graben development in SW Turkey, as pointed out by Ates¸et al (1996), and also highly magnetized bodies in the upper crustal levels revealed by Dolmaz (2007) through the examination of the crust thermal structure in the Burdur-Isparta area using the CPD estimates from aeromagnetic data, may indirectly point to the presence of lower-crust partial melts.…”
Section: Discussionmentioning
confidence: 92%
“…Dolmaz (2007) suggested from an analysis of Bouguer gravity anomalies that the crustal thickness in SW Anatolia changes between 33 km and 37.5 km. Gürer and Bayrak (2007) reported that the depth to the Moho discontinuity is ∼40 km in the vicinity of station ISP, based on electrical resistivity observations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation